Understanding lexical meaning in Northern dialects: an analysis of meaning components - Othman, Zul Hanis Yop; Sha’ri, Sharil Nizam; Abd Aziz, Adi Yasran; Husain, Salina (Human Resource Management Academic Research Society, 2024)
The Northern dialect (DU) has a wide variation in lexical usage, which causes difficulties in establishing a consistent definition of certain terms. This non-uniformity can cause confusion and misinterpretation in lexical studies. This study is to describe DU entries that have ambiguity of meaning based on the definition of Kamus Dewan Fourth Edition (KD4) using the theory of component analysis of meaning (1975). The second is to formulate a new meaning that either has similarities or functional differences based on DU in KD4. This study will use a total of 30 staff members from the Federal Agricultural Marketing Authority (FAMA) by using a group sampling method based on criteria that have been set. Respondents will be interviewed to obtain data and the data will be analyzed using theory. The results of the study found that there is a difference in the meaning received by users regarding the DU entry referred to in KD4 with the meaning given by native DU speakers. Overall, the study of the definition of meaning in DU using this theory makes a great contribution in understanding the richness and complexity of the dialect language, as well as how it reflects the social identity and culture of the local community.